Evolution of watershed phosphorus buffering capacity and its response to land-use change in Poyang Lake basin, China - Zhong, Wenjun; Dong, Yue; Wang, Shengrui; Ni, Zhaokui; Wu, Daishe; Yang, Yulong; Deng, Zeyu (Journal of cleaner production, 2022)
The watershed buffering capacity is an important pivot to regulate phosphorus (P) pressure in aquatic environment, and land use is a key factor for its regulation. However, the response mechanism of buffer capacity to land use change remains unknown. Based on the variation of “buffering capacity index” in the Poyang Lake basin from 1990 to 2019, the mechanism of their response relationship was revealed via quantifying watershed P retention threshold and P removal process in different landscapes. Results showed that the watershed P buffering capacity was significantly affected by the scale of landscape subject to certain conditions of net anthropogenic P inputs (NAPI) in the Poyang Lake basin. The decreases in agricultural land, grassland and wetland and the increase of artificial land jointly explained 66.9% of watershed P buffering capacity decrease before accumulative P retention reached the threshold. The contribution of land use to watershed P buffering capacity change decreased to 53.8% when the P retention exceeded the threshold. Decreasing in watershed P buffering capacity was closely related to the increase of P loss in cultivated land, and wetland P removal provided an optimized direction for restoring the watershed buffering capacity. The findings reinforce the understanding of P hysteresis on watershed environment, and provide a policy basis for developing sustainable P management and pollution control from the perspective of optimizing land-use.